1992
DOI: 10.1246/cl.1992.2471
|View full text |Cite
|
Sign up to set email alerts
|

First Crucial Evidence for Apical-Apical Exchange via a Hypervalent Tellurium Ate Complex in the Reactions of Diaryl Tellurides with Aryllithium Reagents

Abstract: Pentafluorophenyl phenyl telluride and 3,5-dichloro-2,4,6-trifluorophenyl phenyl telluride reacted with pentafluorophenyllithium or 3,5-dichloro-2,4,6-trifluorophenyllithium at low temperature to form the corresponding tellurium ate complexes as sole intermediates of the ligand exchange on the hypervalent tellurium centers. In these tellurium ate complexes electron-withdrawing aryl ligands were arranged at apical positions and the ligand exchanges took place between the apical-directing groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…These lzsTe NMR spectra are rationalized in terms of the increase in the electron density at the central tellurium atom of the hypervalent ate complexes as well as the triphenyltellurium ate complex previously reported [3]. On warming the reaction mixture in an NMR tube, these ' "Te NMR signals shift again to 527.5 and 549.6 ppm, which are assigned as those of tellurides (1) and (2) at room temperature, and the ratios are nearly identical to those of the isolated tellurides, demonstrating that the exchange reaction between two carbon ligands takes place at rwm temperature.…”
Section: Results and Discussion Formation O Tellurium Ate Corn Lexes supporting
confidence: 62%
See 2 more Smart Citations
“…These lzsTe NMR spectra are rationalized in terms of the increase in the electron density at the central tellurium atom of the hypervalent ate complexes as well as the triphenyltellurium ate complex previously reported [3]. On warming the reaction mixture in an NMR tube, these ' "Te NMR signals shift again to 527.5 and 549.6 ppm, which are assigned as those of tellurides (1) and (2) at room temperature, and the ratios are nearly identical to those of the isolated tellurides, demonstrating that the exchange reaction between two carbon ligands takes place at rwm temperature.…”
Section: Results and Discussion Formation O Tellurium Ate Corn Lexes supporting
confidence: 62%
“…These tellurium-lithium exchange reactions have attracted considerable attention, since the reactions provide a convenient procedure for the generation of numerous, synthetically useful organolithium reagents, as presented by Sonoda and co-workers [ 13. Furthermore, the mechanism of the exchange reaction has been investigated by Reich et al [2] and Furukawa et al [3]. They have confirmed that the exchange reaction proceeds via two steps involving the initial formation of discrete intermediates, ate complexes of [10-Te-3(C3)], using 'H, 13C, and Te NMR techniques at low temperatures.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Beak and co-workers 6 ,7 rationalized their isotope labeling experiments on aryl bromides by the involvement of S N 2 or of ate complexes and discarded both an ET and a four-center concerted mechanism. Such ate complexes were detected by Reich and co-workers 8,9 and Ogawa et al 10 for iodoaromatics. More recently Boche and co-workers carried out comprehensive ab initio electronic structure calculations on Ph-I-CH 3 (-) and other ate complexes.…”
Section: Introductionmentioning
confidence: 68%
“…On the other hand, for alkyl halides, the iodides, which are the best electron acceptors in the series F, Cl, Br, I are also, by far, the most prone to form ate-type complexes. [8][9][10] As a consequence the ET participation in the reactivity of alkyl iodides is generally not observed (see, however, ref. 30).…”
Section: Issn 1424-6376mentioning
confidence: 99%